Oral manifestations in individuals with COVID-19: literature review (Research, Society and Development, 2022)
Introduction: COVID-19 is an infectious disease that emerged in 2019, caused by the SARS-CoV-2 virus, was decreed in March 2020 by the World Health Organization as a pandemic and has become a global public health problem. Objective: The objective of this article is to carry out a literature review regarding oral manifestations in individuals with COVID-19. Methodology: Google academic, Scientific Electronic Library Online (SCIELO) databases were used; PUBMED; Virtual Health Library (VHL); using keywords like “Oral Manifestations”, “COVID-19”, “SARS-CoV-2”. Results: This disease causes a series of systemic changes, there are studies on the possible relationship between atypical manifestations and SARS-CoV-2. Results and discussions: The studies showed oral manifestations such as: taste disorder, xerostomia/dry mouth, aphthous lesions, plaques, vesicobullous lesions, petechiae, erythema, pigmentation, multiform lesions, desquamative gingivitis, candidiasis, lichen planus and necrosis of the oral mucosa., herpes-like lesions, ulcerative and erosive lesions. Final considerations: Longitudinal studies are needed to confirm the association of manifestations with COVID-19.